(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this paper is to explore into the contributions of Syrian writers, who remained as residents in Germany for one reason or the other. The reason could be mainly of political or social instability, which always results in the economic crisis. It is attempted here to illustrate the characteristics of migration literature in Germany as a whole as well as the specialties found in the novels and stories of Rafik Schami. The picture of homeland and the other patriotic elements along with the oriental inclusiveness is discussed here with a great deal of importance in detail.